PENGARUH TEPUNG DAUN KELOR DALAM RANSUM SEBAGAI PENGGANTI FEED SUPPLEMENT KOMERSIAL TERHADA KUALITAS TELUR PUYUH - Urip Santoso; Eci Cippa Pritisa; Yosi Fenita (Fakultas Pertanian dan Peternakan Universitas Muhammadiyah Bengkulu, 2022)
This study aimed to evaluate the effect of Moringa leaf powder in the ration as a substitute for commercial feed supplements on the quality of quail eggs. This research was conducted from December 2020 to February 2021 at the Commercial Zone Animal Laboratory, Department of Animal Husbandry, Faculty of Agriculture, Bengkulu University. The research design used was a completely randomized design. One hundred and twenty five quails in the production phase were distributed into 5 treatment groups with 5 replications as follows: P0 = the ration without Moringa leaf powder and commercial feed supplements (Control), P1 = the ration contained 0.5% commercial feed supplement, P2 = The ration contained 0.5% Moringa leaf powder, P3 = the ration contained 1.5% Moringa leaf powder, and P4 = the ration contained 2.5% Moringa leaf powder. The results showed that the administration of Moringa leaf powder at a level of 0.5-2.5% had no significant effect on egg weight, egg yolk color, egg yolk index, egg white index, shell thickness and Haugh unit (P>0.05). It can be concluded that 0.5% Moringa leaf powder could replace commercial feed supplements. In addition, higher levels of Moringa leaf powder did not improve the quality of quail eggs. Key words: quail, Moringa leaf powder, egg quality